Mawlānā Luṭfullah Jahāngīrī’s Biography and his Role in the Khatm-e-Nabūwat Movement - Qazi Abdul Manan,; Shah, Syed Mubarak (Journal of Islamic and Religious Studies, 2020)
Mawlānā Luṭfullah Jahāngīrī, born on September 28, 1906, was a renowned scholar of Pakistan. He played a significant part in ceasing the role of Qadiyanis and declared them as non-Muslim in the Law of the Islamic Republic of Pakistan. He was the only son of the famous religious scholar Maulana Abdul Haq. Maulana Lutfullah studied at the famous school The Darul Uloom Deoband, Delhi. He taught at the Islamic University of Banori Town and he was entitled a Sheikh. He preached the Finality of Prophethood and became successful in it because at that time Qadiyaniyat was widespread in the region. In 1953 he was sent to Rawalpindi Jail. He played a vital role in Delhi Muradabad Dialogue as well as in the dialogue with Qadianis in the Zaida District in Swabi and also in the districts of Mardan. He also received the title of Lutfullah Peshawari by Sheikh ul Hadiths Maulana Zarwali khan. He was considered one of the famous scholars of the Deoband Era. He passed away on 8th August 1983.